Metabolite profiling of IMID‐2, a novel anticancer molecule of piperazine derivative: In silico prediction, in vitro and in vivo metabolite characterization using UPLC–QTOF–MS/MS. (14th February 2021) - Panday, Niraj Kumar; Thakkar, Disha; Patel, Sagarkumar; Shard, Amit; Sengupta, Pinaki
Abstract: IMID‐2, a newly identified piperazine‐based anticancer molecule, has been shown to be cytotoxic against various cancer cell lines. The primary aim of this research was to identify and characterize possible metabolites of the molecule formed during biotransformation. A metabolite identification study was first executed using an in silico tool to predict the possible metabolism sites of IMID‐2. Thereafter, metabolites generated in vitro (rat liver microsomes, rat S9 fractions and human liver microsomes) and in vivo (rat plasma, urine and feces) were identified and characterized employing UPLC–QTOF–MS/MS. A total of eight metabolites, among which were six in phase I and two in phase II reactions, were recognized. The plausible structure of the metabolites and probable metabolic pathway have been established based on the mass fragmentation pattern, mass ppm error, ring double bond calculation and nitrogen rule. The majority of phase I metabolites were generated by N ‐oxidation, hydroxylation, oxidative deamination followed by reduction, oxidative dechlorination, N‐ dearylation, and N‐ dealkylation. Glucuronidation played a significant role in the formation of phase II metabolites of the molecule.